HIGH ABILITIES AND GIFTEDNESS IN ADOLESCENTS AND ADULTS WITH AUTISM: A COMPREHENSIVE VIEW - Pessoa de Souza, Carla; Radeck, Ereni (Revista Gênero e Interdisciplinaridade, 2026)
This study seeks to understand the relevance of research focused on the interests and needs of gifted/talented individuals, especially those who face daily difficulties stemming from their cognitive and socio-emotional characteristics. The literature review shows that, although there is increasing attention to gifted/talented individuals during childhood and adolescence, there is still a significant gap in studies and policies directed at young people and adults. Cognitive specificities—such as high learning capacity, complex thinking, and creativity—associated with socio-emotional aspects, such as perfectionism, hypersensitivity, emotional intensity, and heightened critical thinking, can generate challenges in the school, professional, affective, and social areas when adequate support is lacking.